IMPLEMENTASI AKUNTANSI SEBAGAI STRATEGI BISNIS UMKM - Halpiah, Halpiah; Putra, Hery Astika (LP2M Institut Teknologi dan Bisnis Asia Malang, 2022)
This research is motivated by various problems faced by MSMEs in bread, tofu, sasak culinary, cowhide crackers, and welding in the Mataram City Region. Especially the problem of limited access to capital, the absence of preparation of financial statements so that the business that is run is stagnant and does not develop even though it has been occupied for 10-20 years. Therefore, researchers are interested in carrying out research with the theme